2017
DOI: 10.6018/analesps.34.1.275931
|View full text |Cite
|
Sign up to set email alerts
|

Percepción del Tamaño Corporal e Insatisfacción en Niños de 3 a 6 Años: Una Revisión Sistemática

Abstract: Título: Percepción del tamaño corporal e insatisfacción en Niños de 3 a 6 años: una revisión sistemática. Resumen: La imagen corporal es un constructo ampliamente estudiado, sobre todo en lo que se refiere a la percepción e insatisfacción con la propia imagen. La mayoría de las investigaciones se centran en la adolescencia y adultez, aunque los problemas de insatisfacción aparecen cada vez a edades más tempranas. Por tanto, el propósito de este estudio fue analizar los hallazgos más transcendentes sobre insati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
14
0
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(19 citation statements)
references
References 41 publications
2
14
0
3
Order By: Relevance
“…These results confirm that social affiliation promotes positive feelings and healthy life styles [24]. Although previous studies have interpreted social recognition as an extrinsic goal, this study only found a significant effect of dissatisfaction with body image on developing eating disorders and unhealthy eating styles [16,40].…”
Section: Discussionsupporting
confidence: 82%
See 2 more Smart Citations
“…These results confirm that social affiliation promotes positive feelings and healthy life styles [24]. Although previous studies have interpreted social recognition as an extrinsic goal, this study only found a significant effect of dissatisfaction with body image on developing eating disorders and unhealthy eating styles [16,40].…”
Section: Discussionsupporting
confidence: 82%
“…exercising in response to demands from outside [29]. Previous studies have also found significant differences in motivation by sex, showing that men give higher priority to social aspects related to physical exercise, while women show more concern for their image, suggesting that social pressure exerted by communication media through its continual diffusion of stereotyped beauty may cause women to feel the need for being valued by society [40,30].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Actualmente el cuidado del físico y la imagen corporal es un hecho de gran relevancia social (Cantón, 2016;Chacón et al, 2016;León, González, Fernández, & Contreras, 2018;Meneses, & Moncada, 2008;Morrison, Kalin y Morrison, 2004;Nogueira, Salguero, & Márquez, 2017;O'Dea y Abraham, 2000). En la infancia y sobre todo en la adolescencia aparecen multitud de problemas de autoestima derivados de la gran cantidad de cambios que experimenta el cuerpo en esas edades.…”
Section: Introductionunclassified
“…Es decir, las primeras apreciaciones de la IC se aprehenden en casa, una vez que los padres son importantes agentes de socialización que influyen en la elección del ideal corporal, ya sea por modelamiento, retroalimentación o instrucción (Kearney-Cooke, 2002;Tatangelo, McCabe, Mellor y Mealey, 2016). Los datos empíricos señalan que las madres prefieren una figura delgada en hijas, mientras que para los hijos varones la figura real (FR) y la figura ideal (FI) que ellas eligen es normopeso (Gualdi-Russo et al, 2008;León, Gonzalez-Martí, Fernández-Bustos y Contreras, 2018). Otro elemento fundamental es la alimentación, ya que la (47 papás y 48 mamás).…”
Section: Introductionunclassified